ANALYSIS OF ISLAMIC MONETARY POLICY TRANSMISSION ON BUSINESS SECTOR AND MSME PERFORMANCE - Andri Soemitra; Rifki Ismal; Fuadi Fuadi; Haris Al-Amin; Syawal Harianto; Mukhlish Muhammad Nur; Ahmad Fauzul Hakim (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
Study aims to analyze the form and impact of monetary policy transmission on the business world and MSMEs. The data used in the analysis related to the topic of the study were taken from various literatures, both from books and journal articles. The data from various sources were then analyzed using a literature review approach. Based on the results of the analysis, it was found that there were several forms of transmission of sharia monetary policy and other results found that transmission of sharia monetary policy had a positive and significant impact on the real and financial sectors in general and in particular had a positive and significant impact on the business world and MSMEs.